1994
DOI: 10.1007/3-540-58618-0_59
|View full text |Cite
|
Sign up to set email alerts
|

Robust and secure password and key change method

Abstract: This paper discusses issues and idiosyncrasies associated with changing passwords and keys in distributed computer systems. Current approaches are often complicated and fail to provide the desired level of security and fault tolerance. A novel and very simple approach to changing passwords/keys is presented and analyzed. It provides a means for human users and service programs to change passwords and keys in a robust and secure fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, there are many threats associated with the use of username and passwords authentications, identified even as early as dated back to the 1980's (Menkus, 1988;Riddle et al, 1989;Jobusch and Oldehoeft, 1989). Many other studies show the weaknesses in the username and passwords paradigm and the tricks to using an effective and strong password (Adams et al, 1997;Fagin et al, 1996;Hauser et al, 1996;Jablon, 1996). Conklin et al (2004) demonstrated a concept based theoretical, implementable design using memory aides for password security to be used for multiple systems that are connected by a legitimate user's actions.…”
Section: State Of the Artmentioning
confidence: 99%
“…However, there are many threats associated with the use of username and passwords authentications, identified even as early as dated back to the 1980's (Menkus, 1988;Riddle et al, 1989;Jobusch and Oldehoeft, 1989). Many other studies show the weaknesses in the username and passwords paradigm and the tricks to using an effective and strong password (Adams et al, 1997;Fagin et al, 1996;Hauser et al, 1996;Jablon, 1996). Conklin et al (2004) demonstrated a concept based theoretical, implementable design using memory aides for password security to be used for multiple systems that are connected by a legitimate user's actions.…”
Section: State Of the Artmentioning
confidence: 99%